The Conservative Party : from Thatcher to Cameron - Bale, Tim (Polity, 2010)
The Conservatives are back - but what took them so long? Why did the world's oldest and most successful political party dump Margaret Thatcher only to commit electoral suicide under John Major? Just as importantly, what stopped the Tories getting their act together until David Cameron came along? And what did Cameron do that William Hague, Iain Duncan Smith and Michael Howard couldn't or wouldn't? Has the Tory leader changed his party as much as he claims? Or has his leadership involved more compromise - and more Conservatism - than we realise? The answers, as this accessible and gripping book shows, are as intriguing and provocative as the questions. Based on in-depth research and interviews with the key players, Tim Bale explains how and why the Tories got themselves into so much trouble - and how and why they were eventually able to rediscover their winning ways. The answer, he suggests, lies in the people, the power structures, the ideas, and the very different interests of those involved. "The Conservative Party: From Thatcher to Cameron" is a must-read for anyone wanting to understand what makes the Tories tick.
Keywords: Thatcher, Margaret; Major, John Roy; Hague, William; Smith, Iain Duncan; Howard, Michael; Cameron, David; konservatiivipuolueet : Iso-Britannia; konservatismi : Iso-Britannia; puoluejohtajat : Iso-Britannia; historia : Iso-Britannia : 1945-